2008
DOI: 10.1100/tsw.2008.140
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Myelination in the Central Nervous System

Abstract: Myelin abnormalities that reflect damage to developing and mature brains are often found in neurological diseases with evidence of inflammatory infiltration and microglial activation. Many cytokines are virtually undetectable in the uninflamed central nervous system (CNS), so that their rapid induction and sustained elevation in immune and glial cells contributes to dysregulation of the inflammatory response and neural cell homeostasis. This results in aberrant neural cell development, cytotoxicity, and loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 254 publications
(235 reference statements)
3
89
1
4
Order By: Relevance
“…[3][4][5][6] Cerebral ischemia initiates an inflammatory cascade in the brain that is associated with increases in pro-inflammatory cytokines including tumor necrosis factor-α, interleukin-1β (IL-1β), and interleukin-6 (IL-6). 7 Increases in systemic, vascular, and endogenous parenchymal proinflammatory cytokines could exacerbate perinatal brain damage. 3 Interleukin-1β is one of the key pro-inflammatory cytokines that contributes to acute hypoxic-ischemic injury in the developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Cerebral ischemia initiates an inflammatory cascade in the brain that is associated with increases in pro-inflammatory cytokines including tumor necrosis factor-α, interleukin-1β (IL-1β), and interleukin-6 (IL-6). 7 Increases in systemic, vascular, and endogenous parenchymal proinflammatory cytokines could exacerbate perinatal brain damage. 3 Interleukin-1β is one of the key pro-inflammatory cytokines that contributes to acute hypoxic-ischemic injury in the developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is highly upregulated in active MS lesions [86] and was shown to be expressed by MoMF or microglia, as well as astrocytes [87]. Numerous studies found TNF-α to be detrimental in EAE, although it was also reported to be associated with decreased clinical symptoms [88]. Moreover, TNF-α was associated with anxiety behavior in MOG-immunized mice [89].…”
Section: Macrophage/microglia Activation During Challengementioning
confidence: 96%
“…Oligodendrocyte precursors are more susceptible to oxidative stress than other glial cell types (35). Cytokines produced by glial cells also significantly impact oligodendrocyte function and are linked to inflammatory white matter disorders (36). To begin to elucidate the mechanisms underlying the premature death of oligodendrocytes, we measured mRNA expression of key genes involved in antioxidant defense and inflammatory stress.…”
Section: Diminished Oxidative Defense In Combination With Neuroinflammentioning
confidence: 99%